PRODUKSI BIOETANOL OLEH Saccharomyces cerevisiae FNCC 3210 PADA MEDIA MOLASES DENGAN KECEPATAN AGITASI DAN AERASI YANG BERBEDA - Jay Jayus; Iga Vivin Noorvita; Nurhayati Nurhayati (JURNAL AGROTEKNOLOGI, 2016)
One alternative way to increase the production of bioethanol in molasses is by varying the agitation speed and aeration rate during the fermentation process. The aims of this research were to evaluate the productivity of bioethanol fermentation of S. cerevisiae FNCC 3210 under different agitation speed and aeration rate. The research was carried out under aeration rate of 0.1; 0.3; and 0.6 vvm; as well as agitation speed of 100, 200 and 300 rpm. Microbial concentration, reduction sugar content and ethanol production were observed every 4-hour interval during 24 hours fermentation time. The results showed that the aeration rate treatment was significantly affecting the ethanol production, while the agitation speed was not. Fermentation condition of 100 rpm agitation speed and 0.3 vvm aeration rate released the highest ethanol production (5.43%), and microbial concentration of 4.07 g/L. Keywords: Saccharomyces cerevisiae, bioethanol, agitation speed, aeration rate